Safety evaluation of a food enzyme containing endo‐polygalacturonase and pectin lyase activities from the non‐genetically modified Aspergillus tubingensis strain NZYM‐PE - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme with the declared activities endo‐polygalacturonase ((1–4)‐α‐D‐galacturonan glycanohydrolase; EC 3.2.1.15) and pectin lyase ((1–4)‐6‐O‐methyl‐α‐D‐galacturonan lyase; EC 4.2.2.10) is produced with the non‐genetically modified Aspergillus tubingensis strain NZYM‐PE by Novozymes A/S. It is intended to be used in four food manufacturing processes: fruit and vegetable processing for juice production, fruit and vegetable processing for products other than juices, refined olive oil production and wine and wine vinegar production. Since residual amounts of total organic solids (TOS) are removed during production, dietary exposure was not calculated for refined olive oil production. For the remaining three food processes, it was estimated to be up to 0.132 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level (NOAEL) of 1,430 mg TOS/kg bw per day, the highest dose tested, which when compared with the estimated dietary exposure, resulted in a margin of exposure above 10,833. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and 13 matches were found, including one food allergen (papaya). The Panel considered that, under the intended conditions of use, the risk of allergic reactions upon dietary exposure to this food enzyme cannot be excluded, in particular for individuals sensitised to papaya, but that the risk will not exceed that of consumption of papaya. In addition, oral allergy reactions cannot be excluded in pollen‐sensitised individuals. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.